2020
DOI: 10.1038/s41598-020-79247-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dog–human relationship by combining fMRI, eye-tracking and behavioural measures

Abstract: Behavioural studies revealed that the dog–human relationship resembles the human mother–child bond, but the underlying mechanisms remain unclear. Here, we report the results of a multi-method approach combining fMRI (N = 17), eye-tracking (N = 15), and behavioural preference tests (N = 24) to explore the engagement of an attachment-like system in dogs seeing human faces. We presented morph videos of the caregiver, a familiar person, and a stranger showing either happy or angry facial expressions. Regardless of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 109 publications
(137 reference statements)
2
46
0
Order By: Relevance
“…Therefore, we first compared activation levels associated with the visual presentation of all stimuli compared to implicit baseline (i.e., white cross presented on grey background) using the localizer data set. This revealed taskresponsive activation within the occipital-, splenial-, ectomarginal-, caudal-, medial suprasylvian-and marginal gyri, partially overlapping with results from previous studies investigating face perception [29, [39][40][41][42]57,58] (Fig 1C, Table S1). We then used anatomical masks [51] of these regions as search spaces for the dog participants (Fig 2A).…”
Section: Functional Regions-of-interest (Frois)supporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, we first compared activation levels associated with the visual presentation of all stimuli compared to implicit baseline (i.e., white cross presented on grey background) using the localizer data set. This revealed taskresponsive activation within the occipital-, splenial-, ectomarginal-, caudal-, medial suprasylvian-and marginal gyri, partially overlapping with results from previous studies investigating face perception [29, [39][40][41][42]57,58] (Fig 1C, Table S1). We then used anatomical masks [51] of these regions as search spaces for the dog participants (Fig 2A).…”
Section: Functional Regions-of-interest (Frois)supporting
confidence: 88%
“…Behavioural [7,34,35,44,7073] and imaging studies [58,59] have also demonstrated that dogs are able to perceive facial and bodily cues of dogs and humans and display high responsiveness to ostensive-referential bodily cues [45,46,74,75], already as puppies [76]. Our results do not contradict these findings, but suggest that visual regions involved in the perception of faces are also involved in the perception of other body parts, and may thus encode animate stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…On one end of the spectrum, free-ranging dogs live largely on the outskirts of society, interacting minimally with humans other than to scavenge for food (4). On the other end of the spectrum, pet dogs are welcomed into our homes (5) and beds (6), valued for their companionship, and can evoke emotional reactions analogous to those in the parent-child bond (7)(8)(9). Within this patchwork of human-dog interconnectedness, working dogs represent a small subset of the dog population, but one that can have profound effects on human health and well-being.…”
mentioning
confidence: 99%
“…Based on the results of experiment 1, we decided to compare dogs considered as cooperative workers (here: border collies) to independent workers (here: terriers) in experiment 3. Terriers were chosen because they had shown the initially hypothesized response pattern in experiment 1; border collies because they have been extensively tested in studies on social cognition in our and other laboratories [69][70][71].…”
Section: Discussionmentioning
confidence: 99%